On-filter direct amplification of Legionella pneumophila for rapid assessment of its abundance and viability - Samhan, Farag A. (Water Res, 2017)
Guidelines and regulations to control Legionella pneumophila in cooling water systems of large buildings are evolving due to the increasing number of outbreaks. Rapid, on-site, simple, and sensitive quantification methods that are also able to assess viability may be extremely useful in monitoring and control. Culture-based methods for measuring L. pneumophila may take 4 to 10 days and qPCR-based methods are also slow, requiring at least a day from sample to result, albeit mainly due to the need for sample transport to a centralized laboratory. This study reports a rapid isothermal amplification method for L. pneumophila concentration and detection with live/dead differentiation under field conditions. Using an on-filter direct amplification (i.e., amplification of cells without DNA extraction and purification) approach with propidium monoazide (PMA), and a real time isothermal amplification platform (Gene-Z), L. pneumophila could be detected in 1 to 2 hr at ~1 cfu/100 ml of tap water. Signature sequences from 16S rRNA and cadA genes were used as genetic markers for L. pneumophila and loop-mediated isothermal amplification (LAMP) primers were designed using Primer Explorer V4. Result were also compared with direct amplification of cells spiked into distilled, tap, and cooling water samples as well as extracted DNA by qPCR. This method may be useful to managers of cooling water systems in large buildings for rapid detection of L. pneumophila. The overall approach of on-site sample concentration, on-filter amplification, and live/dead differentiation may be extended to other organisms where analytical sensitivity and speed are equally important.